APLIKASI PENGOLAHAN DATA KUESIONER DOSEN PADA PROGRAM STUDI TEKNIK INFORMATIKA STMIK NURDIN HAMZAH JAMBI - Novhirtamely Kahar; Elvi Yanti (JURNAL AKADEMIKA)
The questionnaire is an assessment tool in the form of a list of questions to obtain information from a number of respondents. The questionnaire data processing Informatics Engineering Program in the process of data input and reporting are still using Microsoft Excel software. This study aims to build Application Questionnaire Data Processing Lecturer at the Department of Information Engineering STMIK Nurdin Hamza program to facilitate and accelerate the process of data processing Lecturer Performance Assessment Questionnaire. This application is built using Delphi 7 Programming Languages ​​and SQLyog as databases. Data input is a lecturer of data, the data subject, the data scale value of each variable question. The input data will be processed through the calculation of the value of the questionnaire and produce the output of the average value calculation results of questionnaires each lecturer. The results showed, with this application, the data processing and reporting of student assessment questionnaire to the lecturer at the Department of Information Engineering STMIK Nurdin Hamzah Jambi become easier, faster and data recording errors can be avoided, so that the process of reporting to the head of study program can be appropriate the specified time.